Formation Behavior of Polyiodine Complex in Photocrosslinked Polyvinyl Alcohol Fiber Spun by Electrospinning Method - Fujisawa, Sho; Yamamoto, Masumi; Kashiwai, Daiki; Azari, Pedram; Khaw, Ying Ying; Gan, Seng Neon; Takahara, Shigeru (The Society of Photopolymer Science and Technology, 2018)
Fiber-oriented film was prepared by electrospinning method using polyvinyl alcohol with stylbazol quaternized group (PVA-SbQ), and the formation behavior of polyiodine complex in fibers was investigated. From the UV-vis spectra and the Raman spectra, it was revealed that PVA-I5 - was formed in the fiber orientated film after staining. It is presumed that in the fiber oriented film, the iodine complexes are aligned in one direction. It is considered that the polyiodine complex is inductively arranged with respect to the orientation of fibers, which contributes to the development of dichroism.